Stage IV Hodgkin's disease presenting with spinal epidural involvement and cauda equina compression as the initial manifestation: Case report - ÇELİKEL, ÇİĞDEM (My University, 1997)
Hodgkin\"s disease very rarely presents clinically, initially with a paraspinal mass, but this should be considered in the differential diagnosis. A patient presenting with back pain was diagnosed to have Stage IV Hodgkin\"s disease. MRI revealed an extradural and intraspinal soft tissue mass with bone infiltration. The importance of MRI in the early evaluation of a paraspinal mass and in determining the extent of the disease is emphasized.
Keywords: Tıp; Dahili Tıp Bilimleri; Fiziksel Tıp ve Rehabilitasyon; Nöroloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Physical Medicine and Rehabilitation; Neurology; Health Sciences; KLİNİK NÖROLOJİ; Klinik Tıp; Klinik Tıp (MED); REHABİLİTASYON; CLINICAL NEUROLOGY; CLINICAL MEDICINE; Clinical Medicine (MED); REHABILITATION; Fizik Tedavi, Spor Terapisi ve Rehabilitasyon; Kayropraktik; Rehabilitasyon; Nöroloji (klinik); Yaşam Bilimleri; Physical Therapy, Sports Therapy and Rehabilitation; Chiropractics; Rehabilitation; Neurology (clinical); Life Sciences; Hodgkin's Disease; spinal epidural involvement; cauda equina compression; MRI; MALIGNANT LYMPHOMA; CORD COMPRESSION; SPACE